2011
DOI: 10.1021/am200049g
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature UV Processing of Nanoporous SnO2 Layers for Dye-Sensitized Solar Cells

Abstract: Connection of SnO₂ particles by simple UV irradiation in air yielded cassiterite SnO₂ porous films at low temperature. XPS, FTIR, and TGA-MS data revealed that the UV treatment has actually removed most of the organics present in the precursor SnO₂ colloid and gave more hydroxylated materials than calcination at high temperature. As electrodes for dye-sensitized solar cells (DSCs), the N3-modified 1-5 μm thick SnO₂ films showed excellent photovoltaic responses with overall power conversion efficiency reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 50 publications
(41 reference statements)
1
43
0
Order By: Relevance
“…The photo-generated take part in the reduction of dissolved oxygen forming superoxide radical anions, O 2 -, yielding hydroperoxy radicals HO 2  on protonation and finally OH  radicals, while the photo-generated holes oxidize the surface hydroxyl group or physisorbed water molecules forming hydroxyl radical, OH  . OH  radicals are a strong oxidizing agent well-known to decompose organic substrates as MB dye [15,37,46]. …”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The photo-generated take part in the reduction of dissolved oxygen forming superoxide radical anions, O 2 -, yielding hydroperoxy radicals HO 2  on protonation and finally OH  radicals, while the photo-generated holes oxidize the surface hydroxyl group or physisorbed water molecules forming hydroxyl radical, OH  . OH  radicals are a strong oxidizing agent well-known to decompose organic substrates as MB dye [15,37,46]. …”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 99%
“…Tin oxide (SnO 2 ) is one of the most intensely studied n-type semiconductor. During the past decade, SnO 2 has been widely used in solid-state gas sensors [11], transparent conducting electrodes [12], rechargeable Li batteries [13], optical electronic devices [14] and solar cells [15]. The structure, bandgap, and chemical stability of SnO 2 are similar to those of titanium dioxide, which is widely used photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…29 The fill factor (FF) does not show any particular variation and but it shows minimum value for 48 h DAT which may be due to interfacial charge recombination. 30 There are very few reports published on bare SnO 2 as a photoanode in DSSCs and all are based on Ru-based sensitizer. 9,21,[30][31][32] The study on dye adsorption time for Eosin-Y sensitized SnO 2 based DSSC is not reported yet.…”
Section: E J-v Characteristics Of Dsscmentioning
confidence: 99%
“…30 There are very few reports published on bare SnO 2 as a photoanode in DSSCs and all are based on Ru-based sensitizer. 9,21,[30][31][32] The study on dye adsorption time for Eosin-Y sensitized SnO 2 based DSSC is not reported yet. Birkel et al 29 recently reported the maximum efficiency (up to 3.2%) with N719 dye sensitized SnO 2 photoanode and observed V oc about 405 mV.…”
Section: E J-v Characteristics Of Dsscmentioning
confidence: 99%
“…Nanocrystalline SnO 2 is an n-type semiconductor 32 with a large band gap (3.6 eV). Due to its unique electrical and 33 optical properties and its chemical stability, SnO 2 is used in dye-34 sensitized solar cells [20], as a photocatalyst [21], in gas sensors 35 [22], etc. In the present study, the Sn loaded Au-ZnO photocatalyst 36 has been prepared through the precipitation-decomposition 37 method.…”
mentioning
confidence: 99%